Process and practice in New Zealand Enviroschool implementation - Proctor, Rachel; Garrett, Joanne K.; Stratford, Robert; Wyatt, Katrina; Williams, Andrew James; Guell, Cornelia (Wellbeing, space and society, 2024)
•Interest in integrating sustainability and health education in schools is growing.•New Zealand's Enviroschools is a socioecological approach to this integration.•This qualitative interview study explores Enviroschools implementation practices and processes via thematic analysis.•Developing meaningful relationships with people and places is key to Enviroschools.•Enviroschools implementation is an experiential, cognitive and affective journey. This qualitative study explores the practices and processes associated with implementing the Enviroschools approach. Enviroschools aim to nurture healthy and sustainable communities through learning and taking action collaboratively. The approach is implemented in over 1600 early childhood centres, primary, intermediate and secondary schools in Aotearoa, New Zealand. Semi-structured interviews were undertaken with 26 participating teachers, school leaders and Enviroschool facilitators and co-ordinators across 6 regions nationwide. Transcripts were analysed through thematic analysis. Two themes were developed to situate and describe participants’ experiences of implementing the approach: forming relationships through attunement and sustaining relationships through critical reflection. Both of these themes speak to the value of applying a relational lens to understand the implementation of systems approaches, particularly in school settings. Our findings also suggest that there is a need for and an appreciation of systems approaches to nurturing wellbeing and sustainability in school communities and that extending systems thinking to the implementation of these approaches can help to bring the interconnections between health and sustainability to life in meaningful ways. The participants valued viewing and approaching implementation as a journey that develops proximal and more distant currents of change over time. Further research to explore the mechansisms of change and how these lead to outcomes may help to translate the practices and processes of implementation.